Integrated DNA methylation analysis reveals a potential role for ANKRD30B in Williams syndrome - Kimura, Ryo; Lardenoije, Roy; Tomiwa, Kiyotaka; Funabiki, Yasuko; Nakata, Masatoshi; Suzuki, Shiho; Awaya, Tomonari; Kato, Takeo; Okazaki, Shin; Murai, Toshiya; Heike, Toshio; Rutten, Bart P. F.; et al. (Neuropsychopharmacology (New York, N.Y.), 2020)
Williams syndrome (WS) is a rare genetic disorder, caused by a microdeletion at the 7q11.23 region. WS exhibits a wide spectrum of features including hypersociability, which contrasts with social deficits typically associated with autism spectrum disorders. The phenotypic variability in WS likely involves epigenetic modifications; however, the nature of these events remains unclear. To better understand the role of epigenetics in WS phenotypes, we integrated DNA methylation and gene expression profiles in blood from patients with WS and controls. From these studies, 380 differentially methylated positions (DMPs), located throughout the genome, were identified. Systems-level analysis revealed multiple co-methylation modules linked to intermediate phenotypes of WS, with the top-scoring module related to neurogenesis and development of the central nervous system. Notably, ANKRD30B , a promising hub gene, was significantly hypermethylated in blood and downregulated in brain tissue from individuals with WS. Most CpG sites of ANKRD30B in blood were significantly correlated with brain regions. Furthermore, analyses of gene regulatory networks (GRNs) yielded master regulator transcription factors associated with WS. Taken together, this systems-level approach highlights the role of epigenetics in WS, and provides a possible explanation for the complex phenotypes observed in patients with WS.